Tinnitus development is associated with synaptopathy of inner hair cells in Mongolian gerbils. (28th June 2021) - Tziridis, Konstantin; Forster, Jan; Buchheidt‐Dörfler, Isabelle; Krauss, Patrick; Schilling, Achim; Wendler, Olaf; Sterna, Elisabeth; Schulze, Holger
Abstract: Human hearing loss (HL) is often accompanied by comorbidities like tinnitus, which is affecting up to 15% of the adult population. Rodent animal studies could show that tinnitus may not only be a result of apparent HL due to cochlear hair cell damage but can also be a consequence of synaptopathy at the inner hair cells (IHCs) already induced by moderate sound traumata. Here, we investigate synaptopathy previously shown in mice in our animal model, the Mongolian gerbil, and relate it to behavioral signs of tinnitus. Tinnitus was induced by a mild monaural acoustic trauma leading to monaural noise induced HL in the animals, quantified by auditory brainstem response (ABR) audiometry. Behavioral signs of tinnitus percepts were detected by measurement of prepulse inhibition of the acoustic startle response in a gap‐noise paradigm. Fourteen days after trauma, the cochleae of both ears were isolated, and IHC synapses were counted within several spectral regions of the cochlea. Behavioral signs of tinnitus were only found in animals with IHC synaptopathy, independent of type of HL. On the other hand, animals with apparent HL but without behavioral signs of tinnitus showed a reduction in amplitudes of ABR waves I&II but no significant changes in the number of synapses at the IHC. We conclude—in line with the literature—that HL is caused by damage to the IHC or by other reasons but that the development of tinnitus, at least in our animal model, is closely linked to synaptopathy at the IHC. Abstract : Hearing loss is often accompanied by comorbidities like tinnitus, but tinnitus can also emerge without hearing loss. A loss of ribbon synapses (synaptopathy) at the inner hair cells can lead to "hidden" hearing loss that is not as easy to detect as "apparent" hearing loss that is often caused by damage to the inner or outer hair cells themselves. We here investigate if tinnitus development in Mongolian gerbils is related to hearing loss or the loss of ribbon synapses at the inner hair cells after a frequency specific acoustic trauma. We find that tinnitus is best explained by synaptopathy and discuss it in the view of a model of tinnitus development by stochastic resonance mechanisms.